A brief survey of the Anjuman-i Islam in Colonial Malaya - Mansor Majdin, Mohamad Firdaus; Zakariya, Hafiz (IIUM Press, International Islamic University Malaysia, 2019)
The Anjuman-i-Islam was established in 1921, following the visit of Khwaja Kamaluddin to Singapore and other states in the Peninsula. This study discusses the establishment of of the Anjuman-i-Islam during the early twentieth century, as a response to the British growing influence in Malaya. The British administrators were cautious in their treatment of the Muslim matters, which were and still are regarded as very sensitive issues. At the same time, they were suspicious of any activity, which could potentially undermine their position in Malaya.. After covering the history of the foundation of the Anjuman-i-Islam, it describes the major activities of this association especially in printing. Moreover, it analyses the major achievements as well as challenges facing this Islamic accociation. It also examines the membership and leadership structure of the Anjuman-i-Islam. Finally, it analyses the attitude of the Anjuman-I-Islam towards the issue of the Caliphate. This study adopts the method of content analysis by investigating the archival materials (such as diplomatic and official memoirs and diaries, British official records, contemporary newspapers, magazines and periodicals). These primary sources are obtained from the National Archives in Kuala Lumpur and its branches, The Library of University Malaya, The Za’ba Memorial Library, The National Archives of United Kingdom, and The British Library.